2017
DOI: 10.1590/1678-457x.15416
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characteristics and fibril-forming properties of collagen from paddlefish (Polyodon spathula) and globefish (Fugu flavidus) skin byproducts

Abstract: Acid-soluble collagen (ASC) and pepsin-soluble collagen (PSC) from the skin byproducts of paddlefish (ASC-P and PSC-P) and globefish (ASC-G and PSC-G) were purified and characterized. The imino acid contents of ASC-P, PSC-P, 197.9, 186.4 and 189.7 residues/1000 residues, respectively. SDS-polyacrylamide gel electrophoresis (SDS-PAGE) and Fourier transform infrared spectroscopy (FTIR) confirmed that all four samples composed of two different α1-and α2-chains with integrated triple-helical structure. Denaturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…Amide A for cobia skin ASC extracted by 0.5 M lactic acid present at wavenumber of 3,478.22 cm −1 was in agreement with study conducted by Wang et al. (2017) which stated the range for general wavenumber amide A of collagen occurred in the range of 3,400–3,440 cm −1 . The existence of amide A in the range of general wavenumber of amide A indicated the well maintained of secondary structure of collagen (Pal & Suresh, 2017; Sampath Kumar et al., 2017).…”
Section: Resultssupporting
confidence: 90%
“…Amide A for cobia skin ASC extracted by 0.5 M lactic acid present at wavenumber of 3,478.22 cm −1 was in agreement with study conducted by Wang et al. (2017) which stated the range for general wavenumber amide A of collagen occurred in the range of 3,400–3,440 cm −1 . The existence of amide A in the range of general wavenumber of amide A indicated the well maintained of secondary structure of collagen (Pal & Suresh, 2017; Sampath Kumar et al., 2017).…”
Section: Resultssupporting
confidence: 90%
“…F1 and F2 brasiliensis skin and bone collagen to the pepsin treatment (Li et al 2013;Ahmad and Benjakul 2010). The electrophoretic pattern of S. brasiliensis collagen corresponds with type I collagen, as previously reported for the skin of other fish species (Ahmad and Benjakul 2010;Wang et al 2017).…”
Section: Collagen Extraction: Yield and Characterizationsupporting
confidence: 79%
“…Our SDS-PAGE result of starfish collagen was also similar to the polypeptide patterns of pepsin soluble collagen (PSC) from the body wall of crown-of-thorns starfish ( Acanthaster planci ) ( Tan et al, 2013 ). The SDS-PAGE result of lumpfish collagen was comparable to polypeptide pattern of collagen from skin of fishes such as paddle fish ( Wang, Sun, & Zhou, 2017 ), golden carp ( Ali, Kishimura, & Benjakul, 2018 ) and channel catfish ( Tan & Chang, 2018 ). Also, the result showed that the polypeptide pattern of collagen samples was not affected by the type of precipitation method.…”
Section: Resultsmentioning
confidence: 60%